Lisocabtagene maraleucel for R/R LBCL in patients not intended for HSCT: final results of the phase 2 PILOT study - Alison Sehgal; Daanish Hoda; Peter A. Riedell; Nilanjan Ghosh; Mehdi Hamadani; Gerhard C. Hildebrandt; John E. Godwin; Patrick M. Reagan; Nina D. Wagner-Johnston; James Essell; Rajneesh Nath; Scott R. Solomon; et al. (Blood Advances)
Abstract: We report final analysis results from the PILOT study of lisocabtagene maraleucel (liso-cel) for patients with relapsed/refractory (R/R) large B-cell lymphoma (LBCL). Sixty-one adults with R/R LBCL who had received 1 previous line of therapy and met ≥1 hematopoietic stem cell transplantation (HSCT) not intended criterion. Overall response rate (primary end point) was 80%; 54% achieved complete response. After median on-study follow-up of 18.2 months, median duration of response was 23.3 months (95% confidence interval [CI], 6.2 to not reached [NR]). Median progression-free survival (PFS) was 9.0 months (95% CI, 4.2 to NR), median overall survival (OS) was NR (95% CI, 16.3 to NR), and 18-month PFS and OS rates were 43% (95% CI, 30-55) and 59% (95% CI, 45-70), respectively. In the treatment-emergent (TE) period (≤90 days after liso-cel administration), 79% had grade ≥3 adverse events (AEs), 38% had cytokine release syndrome (2% grade 3; no grade 4/5), 31% had neurological events (5% grade 3; no grade 4/5), and 7% had grade ≥3 infections. Of 57 patients in the post-TE period (≥91 days after liso-cel administration), 18% experienced grade ≥3 AEs; 1 patient had grade ≥3 infections. Thirty patients in the leukapheresis set (n = 74) died, mostly of disease progression (n = 24). In this population with high incidence of high-grade B-cell lymphoma, primary-refractory disease, advanced age, and comorbidities, liso-cel demonstrated durable efficacy and a favorable safety profile, consistent with previous reports. These results support liso-cel as second-line therapy for this underserved population of patients with R/R LBCL not intended for HSCT. This trial was registered at www.clinicaltrials.gov as #NCT03483103.